Mn(OAc)3 Induced C-4 Arylations of Quinazoline 3-Oxides with Arylboronic Acids - Samandram, Rashinikumar; Çetin Korukçu, Meliha; Coşkun, Necdet (Synthesis, 2021)
The use of manganese triacetate as an oxidant component in the C-4 arylations of 2-aryl-quinazoline 3-oxides with arylboronic acids is reported. The new protocol was applied to prepare new 2,4-diarylated quinazoline 3-oxides in good to high yields. The method was shown to tolerate various substituents on both aromatic rings, and no complications such as deoxygenation or rearrangement to quinazolin-4(3H)-one was observed.
Keywords: quinazoline; quinazoline 3-oxide; C–H activation; arylation; arylboronic acids